A Study on Cosmetic Products Marketed in Iraq: Microbiological Aspect - Raghad A. Razooki; Ebtihal N. Saeed; Heyam Hamza (College of Pharmacy University of Baghdad, 2017)
Cosmetic products contain variable amounts of nutrients that support microbial growth. Most contaminants   in   cosmetic   products   include bacteria such as Staphylococcus, Pseudomonas, Klebsiella,   Achromobacter   and   Alcaligenes. Contaminated water  is  a  likely  source  of organisms found in cosmetic products. Products such as shampoo, hand and body lotion, facial cleanser,  and liquid soaps were analyzed. In this study, out of 60 cosmetic products analyzed, 26.4% were found to be contaminated.    Most of the contamination was from bacteria and no fungal contamination was detected.  The highest level of contamination occurred in shampoo.Viable bacterial were not recovered from 100%, 92.8%, 91.6% and 89.2% of showed bath soaps, facial cleanser, hand and body lotion and shampoos, respectively. Coliforms were recovered from one sample of shampoos. One isolate of shigella and pseudomonas aeruginosa was detected from two samples of shampoo. Keywords: Microbial contamination, cosmetic